Reactualization of Dakwah in The Era of The Industrial Revolution 4.0 Through Training in Graphic Design of Dakwah Content - Aep Kusnawan; Akmal Athallah; Fathya Zulva Fadlilah Salma (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2022)
This study aims to describe efforts to prepare Da'wah Human Resources (HR) in the field of information through graphic design training among teenagers under the auspices of the Bandung ITSAR Youth Foundation. The method used in this research is descriptive by providing a narrative description of what happened in training. The results of the study indicate that to strengthen expertise in the field of graphic design that contains da'wah content, the participants are teenagers who are members of the spiritual field. The training is conducted online through the preparation, process, and evaluation stages. The methods applied are presentation, discussion, and practice. The implications of this research show that the challenges of the Industrial Revolution 4.0 situation, which are used as opportunities for teenagers at the Bandung ITSAR Foundation, can attract participants' interest and produce works of sufficient quality and value in actualizing da'wah in the Industrial Revolution 4.0 Era. Thus, this kind of training is feasible to be developed for youth in various places.